Emergency orthopaedic surgery in the pandemic era: A case series at Cipto Mangunkusumo national tertiary hospital in Jakarta, Indonesia. (2020) - Kamal, Achmad Fauzi; Widodo, Wahyu; Kuncoro, Mohamad Walid; Karda, I. Wayan Arya Mahendra; Prabowo, Yogi; Habib, Hadiki; Liastuti, Lies Dina; Trimartani,; Hutagalung, Errol Untung; Saleh, Ifran; Tobing, Singkat Dohar A.L.; Gunawan, Bambang; et al.
Highlights: There are yet any evidence regarding effects of emergency surgery on COVID-19 spread and benefits in delaying it. Emergency orthopaedic surgery was not associated with increased COVID-19 cases. We suggest performing PCR-RT swab examination for etiological diagnosis in pre-operative settings in future studies. Abstract: Introduction: Every emergency surgery performed is aimed at saving lives; however, during COVID-19 pandemic, surgeries are often postponed. Many existing recommendations take into account postponing surgery during a pandemic. How these surgeries can lead to increasing infection rates has not been widely published. This study aims to investigate the relationship of emergency orthopaedic surgery and the incidence rate of COVID-19. Presentation of case: This was a case series of 14 patients. The study was performed at the emergency department unit at a national tertiary hospital in Jakarta, Indonesia. A total of 14 patients underwent orthopaedic surgery in the emergency room of our institution. The mean age of the subjects was 40.07 ± 20.5 years. Twelve (85.7%) were male patients and 2 (14.3%) were female patients. The average duration of surgery was 125 minutes. The most used type of anaesthesia was general anaesthesia for 6 operations (50%). Patients were hospitalized for an average length of 4 days. Three patients had infiltrates found on plain x-ray examination, which required further examination to determine whether the cause was COVID-19 infection or not. There was no ground glass appearance (GGO) in the three patients in further follow-up examination. Conclusions: We found that emergency orthopaedic surgery was not associated with increasing number of COVID-19 cases. Factors including duration of surgery, length of stay, types of anaesthesia and comorbidities were also not associated with COVID-19 cases in this study.